Peningkatan Minat Belajar Melalui Penerapan Model Pembelajaran Project Based Learning dalam Mata Pelajaran Agama Islam pada Siswa Kelas IV SD Muhammadiyah 3 Unggulan - Tiara Islamiati; Deprizon Deprizon; Radhiyatul Fithri (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Interest in learning has significant urgency in the context of individual development. Students who have a high interest in learning tend to more easily overcome learning obstacles, have the desire to continue learning, and are able to develop their potential to the maximum. The aim of this research is to determine the increase in students' interest in learning in the fourth grade Islamic Religion subject at SD Muhammadiyah 3 Unggulan Pekanbaru after implementing the Project Based Learning (PBL) learning model. This type of research is Classroom Action Research (PTK). The subjects who were respondents in this research were 28 students from class IV of SD Muhammadiah 3 Unggulan, namely 13 male students and 15 female students. After implementing the Project Based Learning (PBL) model, students' interest in learning Islamic Religious Education in class IV of SD Muhammadiyah Unggulan Pekanbar has increased with an average score of 4.6. This increase started from the pre-cycle, namely 2.5, then the Project Based Learning (PBL) model was applied through cycle 1, increasing to 3.3 and continued in cycle II to 4.6, with a significant increase.